Booked for death : a book lover's B & B mystery - Gilbert, Victoria (Gilbert, Victoria. Booklover's B&B Mysteries, 2020)
"Nestled in the historic waterfront town of Beaufort, North Carolina, Chapters Bed-and-Breakfast is a reader's paradise. Built in 1770, the newly renovated inn hosts a roster of special events celebrating books, genres, and authors. It's the perfect literary retreat--until a rare book dealer turns up dead in the carriage house during a celebration of Golden Age mystery author Josephine Tey. The victim's daughter points the finger at forty-two-year-old widow and former schoolteacher Charlotte Reed, who inherited the B&B from her great-aunt Isabella. Charlotte is shocked to discover that the book dealer suspected Isabella of being a thief who founded Chapters on her ill-gotten gains. Charlotte has successfully learned the B&B business in a year, but nothing has prepared her to handle a death on the premises. Armed with intelligence and courage and assisted by her vibrant older neighbor, a visiting author, and members of a local book club, Charlotte is determined to prove her innocence and to clear her great-aunt's name. But the murderer is still at large, and equally determined to silence anyone who might discover the truth behind the book dealer's death. Now, Charlotte must outwit an unknown killer--or end up writing her own final chapter." -- Provided by the publisher.